Challenges of Artificial Intelligence Adoption in Tax Administration - Bensaci, Nadhira; Khenouf, Akram (Journal of Ecohumanism, 2026)
This study aims to analyze the main challenges associated with the adoption of artificial intelligence (AI) in tax administration. The research is based on a systematic review of more than 86 relevant scholarly studies. The findings indicate that tax administrations face multiple challenges in adopting AI, including a shortage of qualified human resources and specialized skills, difficulties in effectively leveraging big data, and ethical concerns related to the privacy of individuals and businesses. Furthermore, political and legal challenges associated with data regulation, organizational culture, technological innovation constraints, environmental, economic, and social factors, difficulties in interpreting AI-generated results, and institutional challenges also influence the adoption process. This study contributes to a clearer understanding of these challenges and emphasizes the importance of addressing them to ensure the successful adoption of artificial intelligence, enhance administrative efficiency, and improve the quality of services provided to taxpayers.